Virulence-associated genes and antibiotic susceptibility among vaginal and rectal Escherichia coli isolates from healthy pregnant women in Poland - Kaczmarek, Agnieszka; Skowron, Krzysztof; Budzyńska, Anna; Gospodarek-Komkowska, Eugenia (Folia microbiologica, 2018)
Vaginal and/or rectal Escherichia coli colonization of pregnant women is sometimes associated with neonatal infections. Despite the relevance of these strains, they have been rarely described before. Thus, the aim of this study was to compare vaginal (VEC) and rectal E. coli (REC) isolates in respect of antimicrobial susceptibility and the frequency of virulence-associated genes (VAGs). The antimicrobial susceptibility of 50 VEC and 50 REC isolates was performed by using the disc diffusion method, and VAGs were detected by PCR. There were no significant differences in the antimicrobial resistance between VEC and REC. Both VEC and REC isolates were mostly resistant to ticarcillin (36 and 30%) and ampicillin (36 and 22%). None of the tested isolates was positive for ESBL. Gene's fimH, fimA, sfa/foc, iutA, ibeA, hlyF, and neuC were detected, respectively, in 98, 92, 32, 28, 12, 8, and 2% of VEC and in 94, 72, 12, 34, 8, 10, and 8% of REC isolates. The co-occurrence of fimA/H and sfa/foc genes was significantly more prevalent among VEC isolates, in comparison to REC isolates. The study indicated that VEC and REC isolates are quite similar in terms of antimicrobial non-susceptibility and VAGs.
Keywords: Microbial Sensitivity Tests; infekce vyvolané Escherichia coli; Pregnancy Complications, Infectious; Escherichia coli Infections; DNA bakterií; Pregnancy; Humans; Genes, Bacterial; Female; Rectum; Polsko; mikrobiální testy citlivosti; infekční komplikace v těhotenství; Escherichia coli; lidé; antibakteriální látky; Poland; faktory virulence; Vagina; vagina; DNA, Bacterial; ženské pohlaví; Anti-Bacterial Agents; Drug Resistance, Bacterial; bakteriální geny; těhotenství; bakteriální léková rezistence; rektum; Virulence Factors